T serotyping of group a streptococcus isolated from patients with pharyngitis or streptococcal toxic shock syndrome in Japan between 2005 and 2017. Issue 2 (February 2020) - ,; Morimoto, Yo; Ogawa, Keiko; Konno, Takayuki; Iwabuchi, Kaori; Seto, Junji; Hoshi, Toshinobu; Kimura, Yuki; Kikuchi, Ryouko; Yamamoto, Kazunari; Nagata, Miki; Funatogawa, Keiji; et al.
Abstract: Streptococcus pyogenes (group A streptococcus; GAS) is an important gram-positive human pathogen capable of causing diseases ranging from mild superficial skin and pharyngeal infections to more severe invasive diseases, including streptococcal toxic shock syndrome (STSS). GAS produces a T protein, and T serotyping has considerable discriminatory power for epidemiological characterization of GAS. To clarify the relationship between STSS and pharyngitis in Japan, we examined the T serotypes of GAS strains isolated from clinical specimens of streptococcal infections (STSS, 951 isolates; pharyngitis, 16268 isolates) from 2005 to 2017. The most prevalent T serotype from pharyngitis isolates was T12, followed by T1, T4, and TB3264. The most prevalent T serotype from STSS isolates was T1, followed by TB3264. Trend of increase and decrease in the frequency of T1 or TB3264 isolation from pharyngitis was correlated with that of STSS patients. The increase of T1 or TB3264 strain-infection in pharyngitis patients may increase the probability of causing STSS, indicating that careful monitoring of GAS serotypes is essential for the prediction of rapid increase of STSS in time to develop effective management strategies.